Social media information and hotel selection : integration of TAM and IAM models / Dayang Nadiah Abang Othman, Arni Abdul Gani and Nur Farahwati Ahmad - Abang Othman, Dayang Nadiah; Abdul Gani, Arni; Ahmad, Nur Farahwati (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
The use of social media as an avenue for marketing and promotion is an emerging phenomenon in the hospitality industry. Lately, an increasing number of consumers have been using social media to connect with others and to share information on their experiences using variety of services in the hospitality and tourism industry. It is argued that many of consumers are now relying on reviews and information found on social media to make informed decision on variety of vacation decisions. The aim of this paper is to identify how web-based social networking can turn into the primary instrument for achieving quick and detailed information for the choice of hotel and to what extent consumer’s acceptance to use information technologies by giving issues to researchers and practitioners.The paper suggested integration of Technology Acceptance Model (TAM) and Information Acceptance Model (IAM) models to understand the issue under study. The research method to be undertaken also highlighted in this paper.